Knowledge Regarding Self-Care among Chronic Obstructive Pulmonary Disease Patients in Selected Hospitals of Hisar, Haryana - Uma Rani, (Innovational: Journal of Nursing and Healthcare, 2025)
Introduction: Chronic obstructive pulmonary disease (COPD) is a progressive, debilitating respiratory condition and a leading cause of morbidity and mortality globally. According to the World Health Organization (2024), over 390 million people suffer from COPD worldwide, with more than 3.2 million deaths annually. India carries a significant burden, with increasing prevalence linked to tobacco use, air pollution, occupational exposure, and poor health literacy. Self-care practices–such as proper medication adherence, lifestyle modifications, symptom monitoring, and smoking cessation–are vital to controlling disease progression, reducing hospitalizations, and improving quality of life. However, a large segment of COPD patients remains unaware or poorly informed about self-care measures. This study was conducted to assess the knowledge regarding self-care among COPD patients in selected hospitals of Hisar, Haryana. Methodology: A descriptive cross-sectional study was conducted among 105 COPD patients admitted to selected hospitals in Hisar, Haryana. The purposive sampling technique was used. A ‘Structured Knowledge Questionnaire on Self-Care among COPD Patients’ tool comprising 25 multiple-choice questions on five sections: Disease Knowledge, Medication Adherence, Lifestyle and Diet, Symptom Management and Smoking Cessation was administered. The tool was validated by a panel of 7 experts, including professionals from nursing, respiratory medicine, public health, and statistics. The Content Validity Index was found to be 0.87, indicating high content validity, and the calculated reliability coefficient was 0.81, indicating high internal consistency. Data were analyzed using Statistical Package for the Social Sciences version 25, applying both descriptive (frequency and percentage) and inferential statistics (Chi-square test). Results: Among the 105 participants, 68% were male and 32% female. The majority were above 60 years of age. Education levels varied, with 58% having only primary education. Knowledge scores revealed that 62% had average knowledge, 25% had good knowledge, and 13% had poor knowledge. A significant association was observed between knowledge scores and educational status (P = 0.03). Conclusion: Most of the COPD patients had average knowledge about self-care, with noticeable gaps among the elderly and less educated. Tailored health education interventions are recommended to improve disease management.